ACADEMIC AND NON-ACADEMIC LANGUAGES AT THE BAHRUL ULUM ISLAMIC BOARDING SCHOOL, TANGGAMUS (PERSPECTIVE ANALYSIS STUDY OF SYMBOLIC INTERACTIONISM THEORY) - Khabibul Khoiri; Thameem (Insititut Agama Islam Agus Salim Metro Lampung, 2022)
Humans are social creatures that cannot be separated from the process of interacting with other people to fulfill their needs in society. Likewise, what is done by students who carry out the interaction process at the Bahrul Ulum Islamic Boarding School also has a uniqueness, namely in the form of academic and non-academic language that is in accordance with the culture or binding rules at the Islamic boarding school. However, the language used in Islamic boarding schools is not interpreted as understood by most people. Therefore, language symbols can describe the atmosphere in the pesantren environment, both in the form of activity terms to satire used for advice so that students can become good and noble individuals which are reflected in the way they speak and behave. That is, although the symbols are not interpreted as in general, the language symbols are agreed upon by the residents of the Islamic boarding school to serve as aform of advice or reminder for the students to always obey the rules of the Islamic boarding school so that a conducive and orderly atmosphere will be created and in the end the educational goals of the Bahrul Ulum Islamic Boarding School can be achieved properly